البناء الفني في المسرح الذهني لتوفيق الحكيم مسرحية اهل الكهف نموذجا - خطراوي، حميدة, مشري، نجوى (جامعة الوادي University of Eloued, 2019)
يعالج هذا البحث البناء الفني في مسرح الذهني لتوفيق الحكيم مسرحية أهل الكهف نموذجاً،إذ طرق الحكيم من الباب الواسع فكرتي الموت والإنبعاث وإستقى شخصياتها من مصادر إسلامية فالزمن، هو الأساس في هذه المسرحية ولا يتوقف عند هذا الحد بل تسري نبضاته في جسم النص كله ،وانطلاقا من السميولوجيا أنها لعبة تفكيك وتركيب و تحديد البنيات العميقة التي تختفي وراء البنيات السطحية المتمظهرة دلالياً ،هدفت هذه الدراسة إلى تناول إشكالية: كيفية بناء توفيق الحكيم مسرحية أهل الكهف فنياً ليستوعب أفكار الفعل المسرحي الذهني؟ وقد توزع ميدان الدراسة على مدخل عرفنا فيه "المسرح عند الغرب" وفصل نظري وفيه تطرقنا "المسرح عند العرب والمسرح الذهني عند توفيق الحكيم " وفصل تطبيقي تناولنا فيه تحليل البنية الفنية من خلال الفعل والزمن، مستوى بناء الشخصيات ، المكان، الحوار ،الصراع،وأخيراً عرضنا أهم النتائج المتوصل إليها التي كشفتها الدراسة السيميولوجية لتصل إلى مستويات أكثر عمقاَ في معانيها من خلال إلتحام عناصر بنائها الفني الناجمة عن أزمة الزمن. This research deals with the artistic construction in the theater of the mind to reconcile the wise play the people of the cave model, as the wise way of the door wide ideas of death and resurrection and derived characters from Islamic sources time is the basis in this play, and not stop at this point, but runs its pulse in the body of the whole text, It The purpose of this study is to address the problem: how to build Tawfik Hakim play the people of the cave technically to accommodate the ideas of theatrical act of mind? The field of study was distributed at the entrance where we defined "theater in the west" and a theoretical chapter in which we discussed "the theater of the Arabs and the theater of mind when Tawfiq al-Hakim" and the separation of application The analysis of the technical structure through the verb and the time, the level of character building, the place, the dialogue, the conflict, and finally we presented the most important results reached by the study of the Semimological to reach deeper levels in their meanings through the fusion of elements of its artistic construction resulting from the crisis of time.
Keywords: المسرح الذهني، البناء الفني، السيميولوجية ، توفيق الحكيم; Mental theater, artistic construction, semimological, Tawfiq al-Hakim